Rat control at Felda Sungai Nerek and Felda Jengka 4: case study / Albakri Ahmad Nazri - Ahmad Nazri, Albakri (Faculty of Plantation and Agrotechnology, 2016)
Rattus tiomanicus, R. argentiventer and R. rattus diardii is the most dominant species in Malaysia Oil Palm Plantation. There are two methods that are usually been used to control rats damage are chemical control and biological control. Rodenticide as a chemical control is one of the most common way to prevent rat damage and Tyto alba (Bam Owl) is a biological control to eradicate rats population in the oil palm plantation due to the specific diet for Tyto alba (Bam Owl) is rat.The objectives of these study is to determine whether the rat damage affect the yield of the oil palm in FELDA Jengka 4 and FELDA Sungai Nerek and to compare the effectiveness of rat management between this both estate. The study are based on secondary data from FELDA Jengka 4 and FELDA Sungai Nerek. The outcome of this study indicate that FELDA Jengka 4 are more efficient in controlling rat damage compared to FELDA Sungai Nerek.Based on the result, for effective control of rat, integrated control between chemical and biological control is needed to reduce the rat population efficiently to achieved high yield.